1998
DOI: 10.2105/ajph.88.2.288
|View full text |Cite
|
Sign up to set email alerts
|

The green prescription study: a randomized controlled trial of written exercise advice provided by general practitioners.

Abstract: OBJECTIVES: The purpose of this study was to determine whether written advice from general practitioners increases physical activity among sedentary people more than verbal advice alone. METHODS: Sedentary patients (n = 456) received verbal advice on increasing physical activity and were then randomized to an exercise prescription (green prescription) group or a verbal advice group. RESULTS: The number of people engaging in any recreational physical activity at 6 weeks increased substantially, but significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(144 citation statements)
references
References 23 publications
6
130
0
2
Order By: Relevance
“…Furthermore, exercise has intrinsic benefi ts for students in terms of their own health and wellbeing (Dyrbye, Satele, & Shanafelt, 2016). Although physicians can be eff ective in increasing patients' health-promoting behaviours, including exercise (Elley, Kerse, Arroll, & Robinson, 2003;Harsha, Saywell, Th ygerson, & Panozzo, 1996;Swinburn, Walter, Arroll, Tilyard, & Russell, 1998), less than half of physicians provide physical activity (PA) screening (Sherman & Hershman, 1993;Walsh, Swangard, Davis, & McPhee, 1999) and less than one third of patients report receiving advice about PA within the previous year (Croteau, Schofi eld, & McLean, 2006;Eakin, Brown, Marshall, Mummery, & Larsen, 2004;Wee, McCarthy, Davis, & Phillips, 1999). Physicians' beliefs (Sherman & Hershman, 1993), knowledge (Rogers et al, 2006), and attitudes toward PA advising (Rogers et al, 2002), their confi dence and prior training in PA advising, and their personal lifestyle (Frank, Hedgecock, & Elon, 2004;Frank, Rothenberg, Lewis, & Belodoff , 2000) are the main factors associated with an increased likelihood of physicians' providing PA advice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exercise has intrinsic benefi ts for students in terms of their own health and wellbeing (Dyrbye, Satele, & Shanafelt, 2016). Although physicians can be eff ective in increasing patients' health-promoting behaviours, including exercise (Elley, Kerse, Arroll, & Robinson, 2003;Harsha, Saywell, Th ygerson, & Panozzo, 1996;Swinburn, Walter, Arroll, Tilyard, & Russell, 1998), less than half of physicians provide physical activity (PA) screening (Sherman & Hershman, 1993;Walsh, Swangard, Davis, & McPhee, 1999) and less than one third of patients report receiving advice about PA within the previous year (Croteau, Schofi eld, & McLean, 2006;Eakin, Brown, Marshall, Mummery, & Larsen, 2004;Wee, McCarthy, Davis, & Phillips, 1999). Physicians' beliefs (Sherman & Hershman, 1993), knowledge (Rogers et al, 2006), and attitudes toward PA advising (Rogers et al, 2002), their confi dence and prior training in PA advising, and their personal lifestyle (Frank, Hedgecock, & Elon, 2004;Frank, Rothenberg, Lewis, & Belodoff , 2000) are the main factors associated with an increased likelihood of physicians' providing PA advice.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity interventions based in primary health care, such as exercise on prescription, have been shown to be effective [6][7][8][9] and cost-effective, 10,11 with a cost-utility ratio comparable to many currently-funded pharmaceutical therapies. A systematic review of the cost-effectiveness of physical activity interventions within primary health care was completed in 2002, in which eight studies were identified, published between 1996 and 2002.…”
Section: Introductionmentioning
confidence: 99%
“…patients [14,15], it is not always easy or practical for clinicians to deliver physical activity interventions during a routine office visit. Indeed, there are numerous barriers including limited time, a lack of coding options for health behavior counseling, and minimal training in physical activity and counseling.…”
mentioning
confidence: 99%